Psihološki profil športnih strelcev z zračno puško in zračno pištolo v Sloveniji - Ratnik, Saša Marija (Šport (Ljubljana), 2018)
Since the beginning of modern times, shooting has been one of the sports disciplines at the Summer Olympic Games, and has a long tradition also in Slovenia. Nowadays, it only occurs in sports. The aim of this undergraduate thesis is to study psychological characteristics of the population of the air rifle shooters and the air rifle shooters in Slovenia. The research encompasses the measuring of aggressiveness, personal traits, intelligence, attentiveness and anxiety as a pre-competition state and as a personal trait. 50 shooters from Slovenia have been included into the research. For the purpose of the research they have been divided into groups according to their gender, age and quality status, i.e., they have been divided into groups of top athletes, active athletes and recreational athletes. The results show that there are differences in the mentioned psychological characteristics between the genders, age and quality status. The male shooters are more physically aggressive and female shooters more irritable. There are also differences in their attentiveness capability level % the results show that the shooters% capability increases up to the age of 30. Then it slowly decreases. There are certain differences also between athletes according to their quality status. The top athlete shooters have turned out to be the least aggressive. It has been assumed that there are different psychological profiles according to the quality status groups. The discriminating analysis has turned out to be statistically insignificant; therefore, we cannot talk about various different profiles. Thus the shooters are similar to one another measured according to the psychological traits they own.
Keywords: osebnost; psihologija športa; psihološki profil; strelstvo; športniki